PENERAPAN MODEL PEMBELAJARAN DISCURSUS MULTY REPRECENTACY UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADAMATA PELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN DI KELAS XI SMK BNKP DARO-DARO BALAEKHA TAHUN PEMBELAJARAN 2020/2021 - Ozianus Laia; Sesuaikan Sarumaha; Hemat Zagoto (Universitas Nias Raya, 2020)
Learning models can make it easier for teachers to innovate in delivering subject matter, because students easily accept and absorb the learning delivered by the teacher. This study aims to determine the improvement of student learning outcomes in Pancasila and Citizenship Education subjects through the application of the Discursus Multy Reprecentacy learning model in class XI SMK BNKP Daro-Daro Balaekha for the 2020/2021 academic year. This study uses the type of Classroom Action Research. The research subjects were students of class XI, totaling 33 people. The results showed that in the first cycle it was 66.66% and the second cycle increased to 100%. The increase in the average percentage of mastery learning outcomes has reached the criteria for the success of the action of 75%. The conclusion of the study is that the application of the Discursus Multy Reprecentacy learning model can improve student learning outcomes in Pancasila and Citizenship Education subjects in class XI TKJ SMK BNKP Daro-Daro Balaekha. The researcher gives several suggestions, namely 1) In teaching the teacher should apply the Discursus Multy Reprecentacy learning model in the learning process in the classroom, especially in the subjects of Pancasila and Citizenship Education. 2) In teaching the teacher should pay attention to the activeness of students in learning so that they are able to follow the lesson well.